Empowering the Mental Health of the Elderly Through Local Wisdom Based Reminiscence Therapy - Faiza, Alya Nur; Hamuda, Nailah ’Ilma; Ulsa, Diyan; Dinakaramani, Smita (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
The Elderly is someone who is 60 years old or above and experiences various changes both physically, mentally, and socially. Meanwhile, Yogyakarta is the province with the largest number of elderly groups in Indonesia with a prevalence of 637,353 people as of December 2021. The prevalence of this large elderly group opens up greater opportunities for various problems in the elderly, one of which is psychological problems. This research aims to examine the effectiveness of reminiscence therapy utilizing local wisdom in reducing depression levels among the elderly in Budhi Dharma nursing home, Yogyakarta. In this research, participants are limited to 10 people with particular criteria and randomly assigned into two groups. They’re guided to do several activities during two days of therapy. Depression levels were measured using the Geriatric Depression Scale (GDS) before, after, and two weeks post-therapy. The result is analyzed with the Friedman Test of Repeated Measures, revealed a p-value of 0.273, indicating that the score differences were insignificant in depression levels across the measurement times. These findings reveal that the lack of significant changes happened due to the participants’ selection that was not screened based on their depression level. As a result, the participants were in good mental condition.